(untitled) (Fiep Bulletin - online, 2015)
The present study as a research body education in initial teacher training in higher education. Given this object, issues arise that have caused us to make some inquiries such as: Who is responsible for the education of the body? Does the education of the body is the sole responsibility of physical education? If the physical education course, in most cases, the body treats a piecemeal fashion without bringing the academic context for an education of the senses and the pursuit of corporeality, then there seems to be a need for a pedagogy of the body. From this test, it is necessary to speak through literature search (SEVERINO, 2002) the story and the picture of the body in society; the story of the body in space education and training; overwhelmed the body in teaching and learning spaces; corporeality as essential content for human development and the proposal of a pedagogy of the body. Possible outcomes and considerations of this theme have relevance in educational spaces, since everywhere traversed in life we experience our body and he self educated in time and space. Thus, in all environments we attend the education of the body itself and the other is because we do not have a body and a body. It’s fundamental role of creating spaces for faculty training and the application of a pedagogy of the body, the senses and the education of corporeality. Finally, it is significant that contextualize the body serves as a tool to study a variety of areas that seek, in the sciences, an understanding of the human being.